Partial Discharge Analysis of UBJOM Rembang PLTU Using Roger's Ratio Method - Trisna Wati; Dany Arianto; Santi Triwijaya (Politeknik Piksi Ganesha Indonesia, 2022)
The disturbance of transformers often occurs at the field is named partial discharge. It refers to the spark release in the isolation of internal cavity or surface caused by the potential difference in the transformer isolation. As a result, the quality degradation of isolation material happens. To test it, the researcher employed Dissolved Gas Analysis by Roger's Ratio and Duval Triangle methods. The results demonstrated that transformer GT 10 reached the highest temperature of 417,229⁰C and produced overheating as indicated by paper carbonation and carbon particle formation in the oil (thermal fault 3000C–7000C). Meanwhile, the GT 20 transformer achieved the highest temperature of 169.2307⁰C and the color of paper isolation change to brown (at <300°C). Both transformers were detected getting the failure of partial discharge as the temperatures were more than 150⁰C; in which several gases were formed, including hydrogen and methane gases at around 150⁰C, ethane gas at approximately 250⁰C, ethylene gas at about 350⁰C, and acetylene gas at around 700⁰C. Accordingly, the higher the temperature, the lower the dielectric capacity, where it should function for separating the electrical conductors.